Permanência, continuidade e ressignificação na política pública educacional municipal : um estudo de caso - Bordignon, Luciane Spanhol (2008)
The present dissertation deals about the public politics that reflect the State s action, more specified, the public municipal power when it refers to the guarantee in the society rights in the educational sector, in a period of neoliberal upsurge and in a globalization world context. In this perspective, investigate, by means of a study of case in the education network of the Getúlio Vargas, RS district, the trajectory that has searching the educational public politic in this district, that evidence so peculiar features, could be considered like a continuity politic, because its shape had origin in the end of the last century, in 1993, and continue even had happened politic-partisan alternation. Understand how this was built, identifying the reasons that admitted the survival, by means of different government, and analyzing the evolution, the changes, the permanence, its effects, the local leadership performance and from entities or institutions current in the network, in a period of fifteen years (1990-2004), are the purpose of the present study. The methodology offered (study of case), make it concret quantitative and qualitatively, by means of documental analysis, semi-structured interviews with the managers of the municipal network and with the pedagogical assessory from the municipal instruction network